Three-dimensional characterization of microstructures in a SEM - Drzazga, Wlodzimierz; Paluszynski, Jaroslaw; Slowko, Witold (Measurement science & technology, 2006)
A method for three-dimensional reconstruction and imaging of surface topography in a scanning electron microscope (SEM) is briefly presented. The method is based on the `shape from shadows' approach and is particularly suitable for relatively smooth surfaces, where stereoscopic methods may be less efficient. The authors used a quadruple secondary electron detector system and new numerical procedures for signal processing, which quite effectively curb main errors inherent in the method. Results of experiments prove that the vertical inaccuracy of the reconstructed shape may be reduced below 10% of the view field dimensions, if local surface inclination angles are less than 65DG. Thus, a SEM equipped with the system designed by the authors may serve as a tool for the inspection and measurement of geometrical issues for several classes of micro-mechanical structures.